Growth Pattern and Morphometric Characteristics of Keting Mystus gulio (Hamilton, 1822) in Downstream of Gembong and Rejoso River, Pasuruan, Indonesia - Chandika Lestariaji; Endang Yuli Herawati; Diana Arfiati; Saddam Langkung Djaduk; Priska Ristianadewi; Aang Setyawan Anjasmara; Rahmi Valina (Postgraduate, University of Mataram, 2025)
Keting fish is a type of fish from freshwater which is usually used as a consumption fish or ornamental fish. There is a type of kein, namely from the species Mystus gulio (Hamilton, 1922). Mystus gulio ecosystem is disturbed due to land-use change activities in the river which causes the disturbance of the habitat of Mystus gulio. The purpose of this study is to analyze the long-weight relationship, growth pattern, and condition factors of Mystus gulio in downstream Gembong and Rejoso River. The method used in this study is to sample Mystus gulio from 3 stations on each river based on land use criteria. The research was carried out for 3 months, namely August, September and October 2023. The results of this study show that Mystus gulio caught in these two rivers all have a negative allometric growth pattern (b<3). The average value of the condition factor in these two rivers is 1 which indicates that the condition of Mystus gulio is good. The average growth of Mystus gulio caught in Gembong is relatively larger than Rejoso. The waters quality results of Gembong and Rejoso are still in optimal condition, except for Total Suspended Solid and Lead (Pb).